Kesejahteraan Psikologis pada Remaja Santri Penghafal Al-Quran - Yoga Achmad Ramadhan (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2012)
Psychological Well-Being is a condition where individual able to receive himself/herself just the way it is, creating warm relationship with others, having independence to social pressure, able to control external environment, having meaning in life also make his/her potential into reality continuously. For adolescent who able to pass and conclude the problems faced and compete setting the environment, there would be directed into positive psychological condition and form a good Psychological Well-Being in himself/herself. The research is a qualitative research with phenomenology study approach. Subject used in this research were Al-Qur'an Memorizer Islamic Students of ”Kampung Tilawah” Islamic School (Pesantren). The amount of subjects were five with initial ZN, AY, AZ, IM, and AK. Data collection method used in this research was interview. Data analysis used in this research was qualitative desriptive. Data realibility checking was done using triangulation technique. According to the research, there found that psychological wealth Al-Qur'an Memorizer Islamic student at Islamic School of Kampung Tilawah was variances, where subject ZN and AY are able to accept themselves just the way they are, controlling warm relations with other to fit it with their needs, having purpose, and clear meaning of life, also aware and use their potential in continuous way. While subject IM and AZ are able to control warm relations with other people, able overcome the problems in independent way, able to control environment as they needed, having clear purpose and meaning of life, realizing and accept themselves just the way they are and never felt increasing knowledge. Subject AK is able to create warm relation with other people, live independently in overcoming the problem, controlling environment as he needed, aware and able to use potential in continuous way, but still cannot accept himself just the way he is, and still has not found his meaning of life.Keywords: Psychological Well-Being, Al-Quran memorizer Islamic student